The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0100-54052009000100005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de métodos de inoculação para a avaliação de cultivares de soja a Fusarium tucumaniae

Abstract: Avaliou-se a reação das cultivares de soja, IAS-5, FT-Cometa, CAC-1, Monarca e MG/BR 46 (Conquista), consideradas resistentes, e de FT-Estrela e FT-Cristalina, suscetíveis a F. tucumaniae, por dois métodos. Foram inoculadas plântulas e folhas destacadas de soja através do método de grãos de sorgo e grãos de aveia, respectivamente. As avaliações de severidade da doença foram efetuadas semanalmente utilizando-se escalas de notas tanto para sintomas observados na parte aérea das plântulas como para o sistema radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Asgrow 3427, produced a foliar severity of 4.3 in the first assay, but only 2.5 in the second experiment, based on a rating scale from of 1 to 5. Although inoculations of F. tucumaniae by the detached leaf method were unable to discriminate soybean cultivar resistance to SDS, the soil infested (Franco et al, 2009) and toothpick methods (Arruda et al, 2005) have been shown to be useful for discriminating levels of aggressiveness of this SDS pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asgrow 3427, produced a foliar severity of 4.3 in the first assay, but only 2.5 in the second experiment, based on a rating scale from of 1 to 5. Although inoculations of F. tucumaniae by the detached leaf method were unable to discriminate soybean cultivar resistance to SDS, the soil infested (Franco et al, 2009) and toothpick methods (Arruda et al, 2005) have been shown to be useful for discriminating levels of aggressiveness of this SDS pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Even when cultivars are screened in artificially infested soil, disease incidence is unpredictable due to the sensitivity of symptomology to environmental factors Rupe et al, 1996;Farias Neto et al, 2008). Methods for assessing aggressiveness (i.e., amount of disease induced) in greenhouse studies include using soil infestation by growing the pathogen on sorghum grain (Hartman et al, 1997Huang & Hartman, 1998;Cho et al, 2001;Rupe et al, 2001;Mueller et al, 2002aMueller et al, , 2002bMueller et al, , 2003Aoki et al, 2005;Farias Neto et al, 2008;Franco et al, 2009), oat seeds (Scherm & Yang, 1996), sand-cornmeal Gray et al, 1999;Njiti et al, 2001), culture filtrates (Jin et al, 1996;Li et al, 1999), inoculation via a toothpick method Arruda et al, 2005), colonized agar plugs (Rupe, 1989), a detached leaf method (Franco et al, 2009) and conidial suspensions (Rupe et al, 1996;Njiti et al, 2001). Development of an accurate disease scoring method for screening resistance to these pathogens, in a rapid and uniform way in the greenhouse, is crucial for developing soybean cultivars with broadbased resistance to the SDS pathogens.…”
Section: Introductionmentioning
confidence: 99%